Increasing the reliability of electricity supply of industrial enterprises for the account of application of a quick-running redundant power supply - Vertugin A.A. (Научно-технический вестник Брянского государственного университета)
One of the main tasks to be performed when organizing the operation of the energy system is to ensure high-quality and uninterrupted power supply to consumers. Dips, interruptions and voltage surges of the electrical network are the most common causes of malfunctions in industrial plants and damage to household equipment, causing significant economic damage to both consumers and electricity suppliers.